(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This research sheds light on the internal and external dialogue in Mihyar’s poetry. The reader of his poems can recognize the poet’s point of view on life and the changes that occur in it. Dialogue has a prominent role in Arabic poetry; therefore, we find some poems in Mihyar’s collection that depend entirely on dialogue. The poet thus relies primarily on thought and on dialogue as a method, in order to highlight the creative abilities through which he attempts to intensify the intended meaning, and to focus on the desired goals, through which he seeks to present the events or scenes that support his idea, according to different narrative styles, in addition to his rich record of embodying intellectual and mental trends.